Desarrollo de trajes de seguridad para soldadores de equipos industriales de cocina. - Esther Alejandra Narváez Vargas (2024)
As designers we seek to provide a solution to a problem, in the industrial sector protective equipment is of vital importance, for this we proceed with the integration of a specific safety suit in the welding area for the industrial equipment company "Los Andes" located in the City of Ambato. The main benefit of this research is to provide a solid defense against occupational risks, reducing the incidence of accidents and guaranteeing the health and safety of workers. The reduction in workplace accidents translates into greater operational continuity, minimizing interruptions and associated costs. This approach not only protects employees, but also positions Equipos Industriales Los Andes as an innovative and responsible leader within the industry, reinforcing its competitiveness and attractiveness in the market. The final product of this research is a work suit designed specifically for the industrial kitchen manufacturing industry. This suit meets the highest safety standards, providing a solid defense against the occupational risks inherent to this activity. The use of advanced textiles allows the suit to not only effectively protect workers, but also improve their comfort and functionality during work. With the information collected from data triangulation, the project was developed based on the needs found of the workers who are going to wear the safety suit. The combination of textiles and weights is integrated for a safety suit that meets xvii the requirements of the users, providing security and this allows better performance by workers.